# Converting polar equation to rectangular

• Dec 30th 2010, 09:59 AM
chrisdb
Converting polar equation to rectangular
I know that I usually use r^2=x^2+y^2, x = r cos(t) and y = r sin(t) to convert polar equations to rectangular, but I seem to come to the correct solution.

$r(\theta) = \frac{e \cdot p}{1+e \cdot cos(\theta)}$

e and p are constants

The polar equation is supposed to be an ellipse, but the solution I came up with doesn't seem correct.

$x = r \cdot cos(t)$

$r = \frac{e \cdot p}{1 + e \frac{x}{r}}$

$r(1+e \frac{x}{r}) = e \cdot p$

$r + e \cdot x = ep$

$r = e \cdot x - e \cdot p$

$r = e ( x - p)$

$r^{2} = ( e ( x-p))^{2}$

$x^{2}+y^{2} = ( e ( x-p))^{2}$

Any ideas?
• Dec 30th 2010, 10:25 AM
DrSteve
You have a small error in the fifth line. It should be r=ep-ex. Other than that it looks correct. Your final answer is an ellipse - it's just not in standard form. You can put it in standard form by multiplying everything out, bringing everything over to the left and completing the square.